Wild Myrtus communis L. Fruit By-Product as a Promising Source of a New Natural Food Colourant: Optimization of the Extraction Process and Chemical Characterization - Erika N. Vega; Lorena González-Zamorano; Elena Cebadera; Lillian Barros; Tayse F. F. da Silveira; Guillermo Vidal-Diez de Ulzurrun; Javier Tardío; Almudena Lázaro; Montaña Cámara; Virginia Fernández-Ruíz; Patricia Morales (Foods)
Myrtus communis L., as a wild underutilized fruit, was analyzed for its physicochemical properties and bioactive composition, revealing a high anthocyanin content principally concentrated in the peel. Therefore, the anthocyanin extraction conditions through ultrasound-assisted extraction from Myrtus communis L. fruit peels (MCP), considered a by-product, were optimized using response surface methodology (RSM), evaluating four independent extraction variables with total anthocyanin content as the response criterion. As a result, optimal extraction conditions were determined to be 20 min, pH 6, 500 W, and 19.68 g/L, yielding a total anthocyanin content of 47.51 mg cya-3-glu/g. In addition, the optimized colourant extract presented a higher content of bioactive compounds compared to the fruit itself, with 1.4 times higher polyphenols and 1.8 times higher total anthocyanin content, with malvidin-3-O-glucoside as the predominant anthocyanin, evidencing the effectiveness of the proposed extraction process. In conclusion, applying the optimal extraction conditions for MPC enables the production of an extract with remarkable anthocyanin content and other phenolic compounds, making it an excellent candidate as a natural food colourant.